Dominance and submission: Social status biases economic sanctions - Emma von Essen; Eva Ranehill (Stockholm School of Economics, The Economic Research Institute (EFI), 2011)
Social hierarchy is persistent in all almost all societies. Social norms and their enforcement are part of sustaining hierarchical systems. This paper combines social status and norm enforcement, by introducing status in a dictator game with third party punishment. Status is conveyed by surname; half of the third parties face dictators with a noble name and half face dictators with a common name. Receivers all have common names. We find that social status has an impact on behavior. Our results indicate that low status men are punished to a greater extent than low status women, high status men, or high status women. Interestingly, discrimination occurs only in male to male interaction. For offers below half, or almost half of the allocated resource, male third parties punish male dictators with common names almost twice as much as their noble counterparts. We find no support for female discrimination. This result suggests that social status has important implications for men's decisions to use economic punishment, and that this holds true in situations where reputation or strategic concerns have no importance.
Keywords: C91; D03; D63; 330; Status; punishment; discrimination; Sozialer Status; Soziale Norm; Geschlecht; Strafe; Spieltheorie